Four 19th-Century Steamboats in Shelburne Shipyard, Lake Champlain, Vermont, USA - Kennedy, Carolyn (The international journal of nautical archaeology, 2025)
Three seasons of fieldwork from 2014 to 2016 investigating four steamboat hull remnants in Lake Champlain resulted in a wealth of archaeological insight into the fast-changing development of steamer design and construction in the first half of the 19th century. The wreckages of Phoenix II (1820–1837), Burlington (1837–1853), Whitehall (1838–1852), and A. Williams (1870–1893) were carefully recorded and analyzed, allowing their identities to be verified and revealing extensive differences in construction choices of boats built for the same waterway within a very short time span. The results demonstrate the experimental nature of shipwrights who sought to build the fastest vessels to outpace the competition as passengers demanded more and more speed. By moving from sturdier structures in the 1820s to longer, narrower, and lighter forms in the 1830s and later, shipwrights capitalized on the hulls’ designs to gain increments of speed for their employers.